Large-Scale Mobile Sensing Enabled Internet-of-Things Testbed for Smart City Services - Jorge Lanza; Luis Sánchez; Luis Muñoz; José Antonio Galache; Pablo Sotres; Juan R. Santana; Verónica Gutiérrez (International Journal of Distributed Sensor Networks)
Smart cities are one of the key application domains for the Internet-of-Things paradigm. Extending the Web into the physical realm of a city, by means of the widespread deployment of spatially distributed Internet-addressable devices with sensing and/or actuation capabilities, allows improving efficiency of city services. Vehicles moving around the city become excellent probes when the objective is to gather information across the city in a cost effective manner. Public transportation fleets, taxis, or vehicles such as waste collection trucks cover most of the urban areas with a limited number of vehicles. This paper presents the deployment of a large scale Internet-of-Things testbed that has been carried out in the city of Santander. It extends previous descriptions by providing a specification of one of the unique features of the testbed, namely, the devices that have been installed on 140 buses, taxis, and vans that every day drive around the city. Besides the physical characteristics of the devices installed and the lessons learnt during the deployment, the paper introduces the three mobile sensing network strategies used for distributing the data gathered. Finally, the paper sketches some of smart city services which might be provided using the information coming from the mobile IoT devices.